2015
DOI: 10.2903/j.efsa.2015.4002
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the risks to public health related to the presence of nickel in food and drinking water

Abstract: EFSA received a request from the Hellenic Food Authority (EFET) for a scientific opinion on the risk to human health from the presence of nickel (Ni) in food, particularly in vegetables. The EFSA Panel on Contaminants in the Food Chain (CONTAM Panel) decided to extend the risk assessment also to drinking water. The reproductive and developmental toxicity in experimental animals was selected as the critical effect for the assessment of chronic effects of Ni. A tolerable daily intake of 2.8 µg Ni/kg body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
80
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 392 publications
(450 reference statements)
3
80
1
1
Order By: Relevance
“…Unlike the other vegetables, beans were sold already dried and out of the pod. Of note, EFSA found relatively high Ni concentrations in "legumes, nuts, and oilseeds", and dried beans contained the highest mean concentrations of Ni (41). Most importantly, developing seeds store essential heavy metals, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the other vegetables, beans were sold already dried and out of the pod. Of note, EFSA found relatively high Ni concentrations in "legumes, nuts, and oilseeds", and dried beans contained the highest mean concentrations of Ni (41). Most importantly, developing seeds store essential heavy metals, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…has been established, and no maximum levels are currently established for Ni in food at the EU level (41). EFSA estimated the mean chronic dietary exposure to Ni in the European population between 2.0 and 13.1 μg kg -1 b.w.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally, a study in Greece, revealed high levels of nickel in drinking water from various regions of Greece (35). The European Food Safety Authority (EFSA) reported that nickel is a widespread component of Earth's surface found in all environmental compartments and is ubiquitous in the biosphere (36). Weathering of rocks and soils has been identi ed as one of the main natural sources of nickel (37).…”
Section: Discussionmentioning
confidence: 99%
“…A TDI has also been set for Ni (2.8 μg/kg b.w.) [45]. Based on the samples with the highest concentrations, a person weighing 70 kg can on a yearly basis eat 5.5 kg of perch from Rundvannet, Norway before the TWI for methyl-Hg is reached, assuming that all Hg in the fish sample was methyl-Hg (a high proportion of methyl-Hg was frequently reported to the European Food Safety Authority) [44].…”
Section: Discussionmentioning
confidence: 99%